The Role of Notaries in Preventing the Misuse of Fintech and Crypto Assets for Money Laundering: Risk Analysis and Required Due Diligence Framework - Surya Dharma Ali; Fanny Tanuwijaya; Moh. Ali (International Journal of Law and Society, 2026)
The rapid development of financial technology (fintech) and crypto assets has created a paradox in the global financial system: while promoting inclusion and efficiency, it also opens new vulnerabilities for money laundering offenses. Notaries, as public officials and legal professionals involved in various financial and business transactions, are at the forefront of preventing this misuse. This article analyzes the specific risks of money laundering through fintech and crypto assets and formulates the due diligence framework required by notaries in carrying out their preventive functions. The research method uses a normative juridical approach with doctrinal analysis of regulations and international standards, enriched with case studies and best practice references. The findings indicate that notaries face three main challenges: (1) difficulty in identifying parties in virtual transactions, (2) the volatility and relative anonymity of crypto assets, and (3) the gap between the speed of technological innovation and regulatory adaptation. This article proposes an Enhanced Digital Due Diligence (ED3) model that integrates digital verification technology, blockchain forensic analysis, and a dynamic risk-based approach. This framework is expected to strengthen the role of notaries as gatekeepers in the rapidly evolving digital financial ecosystem while maintaining the profession's relevance in the era of digital transformation.